Persepsi Orang Tua Rantau Terhadap Pendidikan Anak - Yanto Yanto (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2020)
This research is motivated by the results of observations in XXX Village, Waru Subdistrict, Pamekasan Regency, where the most of the community have a profession as an immigrant with various abilities. This research focuses on the expatriate dentist who works in various parts of this country. because it's easier to find respondents to get data research we need. This research focuses on the expatriate dentist who works in various parts of the archipelago. because it's easier to find respondents to get the research data they need. This tradition, if we examine further will affect the educational conditions of children left at home. Therefore, this research wants to find out how they really feel about children's education? In Another side, children's education is an important thing that should get the attention of the parents. Because parental education is very big effect on children's education, in their intellectually, spiritually, and character. This research uses a qualitative-descriptive approach by collecting data using interviews and observations and the data are analyzed using content analysis techniques. The results show that: 1) the lack of parental knowledge about children's education; 2) children's educational responsibilities are borne by the family at home; 3) school institutions are considered to be responsible for children's education; and 4) there is an assumption that meeting economic (financial) needs is a primary need for children. In this study describes perceptions, early childhood education, children's education in Islam, the transfer of family functions, family responsibilities towards children's education, the nature of migrating and its impact on children's education.